MULTILATERAL CONTRACTING AND PREVENTION. (4th April 2013) - Pope, Brandon; Deshmukh, Abhijit; Johnson, Andrew; Rohack, James
ABSTRACT Incentives created through contracts can be used as a means of decentralized control in healthcare systems to ensure more efficient healthcare. In this paper, we consider an insurer contracting with a consumer and a provider. We focus on the trade‐off between ex ante moral hazard and insurance, and consider both consumer and provider incentives in the insurer's contracting problem in the presence of unobservable preventive efforts. We study two cases of provider efforts: those that complement consumer efforts and those that substitute for consumer efforts. In the first case, our results show that the provider must have greater incentives when the consumer is healthy to induce effort and that inducing provider effort allows an insurer to offer a more complete insurance contract relative to the bilateral benchmark. In the second case, we state conditions under which these conclusions continue to hold. On the basis of our findings, we discuss the implications and challenges of multilateral contracting in practice. Copyright © 2013 John Wiley & Sons, Ltd.